A curriculum perspective for Bachelor of Science in Public Health 4-years honors degree program at public and private universities in Bangladesh - Laskar, MS (Mediscope, 2018)
A comprehensive Bachelor of Science in Public Health (BScPH) curriculum containing multidisciplinary modules was seemed to be appropriate for 4-years undergraduate (honors) for public and private universities of Bangladesh exploring to start the program and to flourish public health education. It was explored and developed one reviewing well-established learning objectives of public health education and curriculum development by different universities around the world. Focusing on multidisciplinary courses, several study topics were derived for this BScPH curriculum such as basic biological subjects, mathematics and other core courses integrating the contribution of arts and sciences disciplines into public health, developing critical thinking and quantitative literacy skills, acquiring personal and social responsibility through incorporation of experiential learning, and providing integrative learning for global health challenges. English is the preferable language medium of instruction. The curriculum contains 156 credit points, which are to be completed by the students for graduation. The curriculum might contribute to establish public health undergraduate (honors) program at public and private universities, which would make more students to come forward to be graduates in the field and serve to build a healthy nation. An evaluation at any point while conducting the BScPH degree program will help to modify or update the curriculum taking into consideration the current situation and information to enhance achieved learning outcome. Mediscope Vol. 6, No. 1: Jan 2019, Page 31-39